The demographic characteristics of Medicaid-eligible uninsured children. - Avruch, S (1998)
OBJECTIVES: This study estimated the number of uninsured children in 1993 who were eligible for Medicaid. METHODS: Data from the March 1990 and 1994 Current Population Surveys were analyzed. RESULTS: At least 2.3 million Medicaid-eligible children were uninsured in 1993. These children were more likely to have a working parent than children on Medicaid. Higher proportions of uninsured children less than 6 years of age, children who lived in female-headed single-parent families, and African-American and Hispanic children were eligible for Medicaid. CONCLUSIONS: Many eligible children do not enroll in Medicaid, and they differ in specific ways from enrolled children.